PENGARUH ASIMETRI INFORMASI, GOOD CORPORATE GOVERNANCE, KEBIJAKAN UTANG DAN PERTUMBUHAN PENJUALAN TERHADAP PRAKTIK MANAJEMEN LABA PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Darmayanti, Susi; Kirmizi, Kirmizi; Savitri, Enni (Fakultas Ekonomi dan Bisnis, Universitas Riau, 2017)
This study aims to examine and analyze the effect of asymmetry of information,good corporate governance is viewed from an independent commissioner and managerial ownership, debt policy and the growth of sales to earnings management practices. The population in this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2009 - 2014. The technique in this study using purposive sampling method using predetermined criteria of the obtained sample of 41 companies. Tests using multiple linear regression models with SPSS 20.The results showed that the asymmetry of information, debt policy and sales growth effect on earnings management practices, while the independent directors and managerial ownership has no effect on earnings management practices.